Kajian Sosial Ekonomi Wanita Pemecah Batu Suplit dalam Menunjang Kehidupan Keluarga (Studi Kasus Pekerja Sektor Informal Pemecah Batu di Kecamatan Moramo Utara Kabupaten Konawe Selatan) - Makmur Kambolong (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
The Study of Women's Socio-Economic Assessment breaking stones Suplit In Supporting Family Life) is a study of the informal sector workers conducted in the form of a survey. This study aims to assess the socio-economic level of the workers, educational level, income levels, health effects, social conditions of households, to assess and analyze the share of income received, identify and examine the issues that arise in doing the job as a stone breaker. The data then grouped into shortages, expectations, and negative impacts. Population and sample research areas: 10 urban villages/villages in the district of North Moramo as population, while the sample area there are five (5) urban/village as places of concentration of workers, namely Lalowaru, Puasana, Mata Wawatu, Sanggula, and Lamokula. The research samples are 5 percent of all households, so the total sample are 93 people scattered in sample villages. Research informant is the head of sub-district of North Moramo, stone processing workers, and transporting stones bus. The data is collected by observation, interview accompanied by a list of questions, as well as documentation of objective conditions. Due to the purpose of the research, descriptive analysis techniques is used to describe and analyze the objective conditions in the field. Results of research shows that female workers are housewives who help to support the family needs. The stone-breaker women are in low education level and even many who never went to school. Income earned by an average of Rp. 30.000,- per day per worker and it is calculated based on how much the stone broken. In doing the job, the women workers use limited safety equipment which are only hammer and gloves. This cause negative impacts for the health of the eyes and lung by inhaling stone-dust every day. Keywords: women breaking stone, socio-economic conditions